The Literacy Groups Project: Investigating the Use of Reading Recovery Techniques with Small Groups of Grade 2 Students - Begoray, Deborah L. (Alberta Journal of Educational Research, 2001)
The two-year Literacy Groups Project provides evidence that grade 2 students can be helped to attain average grade-cohort reading levels by the use of a small-group pull-out program if certain criteria are met. Students were tested using running records at the beginning and end of the study to provide data for quantitative comparison. Additional context was provided by videotaping lessons and interviewing teachers. Major changes took place from the first disappointing year of the project to the second more successful year. First, students were assigned to groups according to a narrow range of Reading Recovery reading levels rather than being randomly placed. Second, the material was found to support fully even highly trained and experienced teachers newly engaged in adapting Reading Recovery techniques to effect accelerated learning in a small-group setting, rather than expecting teachers to follow general program guidelines. In this case, while they were supported in their beliefs about how best to help struggling readers, resource teachers were provided with a commercial reading program, with lesson ideas and multiple copies of leveled student reading materials.